2021
DOI: 10.7150/jca.58726
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of Six Liver Functional Reserve Models to predict Posthepatectomy Liver Failure after Major Resection for Hepatocellular Carcinoma

Abstract: Objective: To validate and compare the predictive ability of albumin-bilirubin model (ALBI) with other 5 liver functional reserve models (APRI, FIB4, MELD, PALBI, King's score) for posthepatectomy liver failure (PHLF) in patients with hepatocellular carcinoma (HCC) who underwent major hepatectomy. Methods: Data of patients undergoing major hepatectomy for HCC from 4 hospitals between January 01, 2008 and December 31, 2019 were retrospectively analyzed. PHLF was evaluated acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In our previous study, we validated and compared the predictive ability of 6 liver function reserve models for PHLF in patients with HCC after major hepatectomy. Our results revealed that although the ALBI score shows more accurate predictive ability, the areas under the receiver operating characteristic curves (AUROC) was only 0.64 ( 14 ), which indicated a limited accuracy. Therefore, development of a more accurate predictive model for PHLF is needed.…”
Section: Introductionmentioning
confidence: 76%
“…In our previous study, we validated and compared the predictive ability of 6 liver function reserve models for PHLF in patients with HCC after major hepatectomy. Our results revealed that although the ALBI score shows more accurate predictive ability, the areas under the receiver operating characteristic curves (AUROC) was only 0.64 ( 14 ), which indicated a limited accuracy. Therefore, development of a more accurate predictive model for PHLF is needed.…”
Section: Introductionmentioning
confidence: 76%
“…Therefore, many studies have focused on the prediction and diagnosis of ICP to enable earlier detection and prevention of ICP. 6,9,16,17,[27][28][29][30] Accordingly, serum levels of irsin, 25 vitamin D3, feutin-B, pregnancy-associated protein-A, and betatrophin have been used as novel biomarkers for the prediction and early diagnosis of ICP. 9,28,29 However, these biomarkers are not in the routine tests of maternal examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Scores were calculated as follows: Aspartate aminotransferase (AST) À platelet ratio index (APRI) score = (AST/upper limit of normal 40 IU/L)/ platelet count  100, 13 MELD score = 3.78  ln (total bilirubin μmol/L) + 11.2  ln (INR) + 9.57  ln (creatinine mg/dL) + 6.4, 14 ALBI score = À0.085  (albumin g/L) + 0.66  (total bilirubin μmol/L). 16 The neutrophil/lymphocyte ratio (NLR) is calculated by dividing the absolute neutrophil count by the absolute lymphocyte count. Platelet/lymphocyte ratio (PLR) is obtained by dividing the absolute platelet count by the absolute lymphocyte count.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiang et al reported a probability of 29.0% of severe PHLF in 186 patients with huge HCC [ 25 ]. Guo et al demonstrated that 13.8% patients experienced PHLF of all grades after major hepatectomy in a total of 745 patients [ 26 ]. In the present study, based on the experience of two centers over a period of 5 years, we reported a double PHLF grade B–C rate after hepatectomy in a large cohort of 611 patients with huge HCC.…”
Section: Discussionmentioning
confidence: 99%